How can we improve the diagnosis and management of bladder pain syndrome? Part 1: ICI‐RS 2018. (2nd October 2019) - Khullar, Vik; Chermansky, Christopher; Tarcan, Tufan; Rahnama'i, Mohammad Sajjad; Digesu, Alex; Sahai, Arun; Veit‐Rubin, Nikolaus; Dmochowski, Roger
Abstract: Background: This paper summarizes the discussion in a think tank at the ICI‐RS 2018 about the diagnosis of bladder pain syndrome (BPS). Aims: To review the guidelines, investigations and subtypes of BPS. Materials and Methods: Review of literature in the light of the think tank discussion. Results: All guidelines recommend completing history, physical examination, urine analysis, urine culture, and urine cytology to define the BPS phenotype but there are differences on further investigations. In those guidelines which recommend cystoscopy, the identification of Hunner's lesions (HLs) is recommended as this changes the treatment plan and outcome. Conclusion: We propose that the differentiation of Hunner's ulcers is an important step in the assessment of these patients. Further suggestions for research are suggested.